On convex functions of order α and type β - Wancang Ma (International Journal of Mathematics and Mathematical Sciences)
Owa [1] gave three subordination theorems for convex functions of order α and starlike functions of order α. Unfortunately, none of the theorems is correct. In this paper, similar problems are discussed for a generalized class and sharp results are given.